(untitled) (Journal of Universal Science Research, 2025)
This article presents information on the role of informatization in various spheres of human activity in society, the social necessity of learning a foreign language in an information educational environment, the possibilities of widespread use of information technologies, the main groups of communicative relations according to their orientation. Also, special attention is paid to the importance of teaching students a foreign language based on modern multifunctional electronic communication tools.